Mixed convection in lid-driven cavity with inclined magnetic field - Bakar, N.A.; Roslan, R.; Karimipour, A.; Hashim, I. (Universiti Kebangsaan Malaysia, 2019)
Effects of magnetic field inclination on fluid flow and heat transfer in a two-dimensional square cavity are analyzed numerically. The vertical walls are well insulated, the bottom wall is maintained at a cold temperature, while the top moving lid is kept at a hot temperature. The finite volume method and SIMPLE algorithm are employed to solve the dimensionless governing equations. The results are presented by the profile of streamlines and isotherms, and the variation of Nusselt number. Mixed convection flow is retarded by the presence of the magnetic field and the average Nusselt number is an increasing function of the magnetic field angle.